2007
DOI: 10.1097/mlr.0b013e31814847a0
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Conducting Complex Clinical Trials in Diverse Community Practices

Abstract: Diverse community primary care practices without support from health system resources will complete participation in complex trials. Researchers need not avoid answering questions requiring complex study designs; however, successful implementation requires an individualized approach tailored to the needs and characteristics of each practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…Multiple clinical trials with 200 and 400 μg per day of inorganic selenium for months to years have shown no toxicity (51, 52). Another study reported no obvious toxicity with doses from 1600 to 3200 μg per day given for 12 months (53). We therefore expect that a dietary supplement of ~200 μg MSC /day, a level currently found in many multivitamin preparations, would be effective in resetting circadian rhythm in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple clinical trials with 200 and 400 μg per day of inorganic selenium for months to years have shown no toxicity (51, 52). Another study reported no obvious toxicity with doses from 1600 to 3200 μg per day given for 12 months (53). We therefore expect that a dietary supplement of ~200 μg MSC /day, a level currently found in many multivitamin preparations, would be effective in resetting circadian rhythm in humans.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33][34][35][36][37][38][39] Few studies have addressed potential benefits for the practice that extend beyond the study topic. As PBRN studies move from simply recording events to evaluating new management strategies and systems, the potential benefits to the practices increase.…”
mentioning
confidence: 99%
“…This cross-sectional analysis is based on the third-year data from control practices in the Using Learning Teams for Reflective Adaptation trial, a group randomized intervention study (Orzano et al, 2007a) aimed at testing a method for improving practice adherence to guidelines for multiple conditions. This trial was approved by the University of Medicine and Dentistry of New Jersey's institutional review board.…”
Section: Methodsmentioning
confidence: 99%